Κολόη und Ḳoɦayto (‘Auf-/Ausblick’): Studien zur äthiopischen Toponomastik. 1 - Voigt, Rainer (Aethiopica, 1999)
The Eritrean place names Ḳoħay-to and Ḳoħay-n contain the root √ḳlħ which can be recognized too in the Old South Arabian place name Ḳlħn. The identity of Ḳoħayto with the classical Κολόη reported by the Periplus Maris Erythraei (1st century A.D.) is based on phonological and semantic considerations. The meaning of the root becomes evident from Sabaen ḳlħ ‘raised water-channel’ as well as from its modern Yemeni Arabic equivalent qalħ ‘upper fields; a water channel through which water is conducted to higher level pipes’. In Tigrinya the same root is attested in several verbal and nominal forms as in ḳwålaɦta ‘upward look with raised head’. This meaning fits very well to the geographic position of Koloë/Ḳoɦayto on the eastern edge of the Eritrean plateau.